El director esta cada vez peor! - Gutman, Dan; Paillot, Jim (Madrid : Bruno, 2018)
A skateboarding principal offers unusual incentives to his students to motivate them to learn more.
Translation of: Mr. Klutz is nuts!
Text in Spanish. Texto en espa?ol.
Keywords: School principals -- Juvenile fiction; Learning -- Juvenile fiction; Schools -- Juvenile fiction; Spanish language materials